Awareness of prevention of teenage pregnancy amongst secondary school learners in Makhado municipality - Giliana M. Maxwell; Makondelele Radzilani-Makatu; James F. Takalani (AOSIS, 2016)
Background: Sexuality plays a very significant role in the lives of both boys and girls. It is, therefore, considered important for schools to recognise and accept sexuality as part of the development process of the child. Professor Kader Asmal (previous South African Minister of Education) suggested that the earlier the school begins to teach learners about sexuality, the better because they can be easily misled by their peers if proper guidance regarding their sexuality is not given. Aim: The current study was conducted to assess the awareness of teenagers on the prevention of teenage pregnancy (TP) in six secondary school learners situated in the Soutpansberg-West circuit, Makhado Municipality in Limpopo province. Setting: The study was conducted at six secondary schools situated in the Soutpansberg-West circuit, Makhado Municipality in Limpopo province in 2014. Methodology: A quantitative descriptive survey study was conducted where data were collected, using self-administered questionnaires, from 381 systematically sampled participants from six secondary schools situated in the Soutpansberg-West circuit, Makhado Municipality in Limpopo province. Data were analysed descriptively using the Statistical Package for the Social Sciences (SPSS) software, version 22.0. Necessary approval procedures and ethical clearance were obtained prior to data collection. Results: Ninety-four percent of participants agreed that TP can be prevented through abstaining from sex, whilst 65% of participants agreed that TP could be prevented by using contraceptives such as pills and injections. Eighty-three percent of participants agreed that T Pcould be prevented through the use of condoms. Seventy-four percent participants disagreed that bathing after sex prevents teenage pregnancies. Furthermore, 28% participants agreed that TP can be prevented by oral sex. Conclusion: The conclusion drawn was that learners are aware of the measures for preventing TP. Keywords: Effectiveness, Sexuality Education, Teenage Pregnancy, Teenagers.